Effects of Cadmium and Sulfur Interaction on Growth and Some Physiological and Qualitative features of Wheat Triticum aestivum L. - Farah Subhi Salih; Anwar Fakhree Altaee; Hanan ِAmeer Alrashide (College of Education for Pure Sciences, 2013)
ABSTRACT This study investigates the effects of treating soil with Cadmium and Sulfur and the interaction between them. It also studies some physiological features of wheat plant in the environment of the plasichouse. The study has come up with the conclusion that the soil treated with Cadmium with concentration (1, 50) ml mol/Kg soil led to a decrease in the dry weight of the shoot and root. Similary it led to an increase in the concentration of chlorophyll a , b and the total chlorophyll (a + b), relative water content, protein, carbohydrates and significant increase proline in the leaf tissues of Wheat plant. There was also a significant increase in the growth since there was an increase in the dry weights of the shoot and root. Like wise there was an increase in the above mentioned features and a decrease in the concentration of proline in the leaf tissues when the soil treated with Sulfur with concentration (1, 2) ml mol/Kg soil as compared with a potential average of (p > 0.05). As for interaction effects it also found that the soil treated with Cadmium and Sulfur concentration (1) ml mol/Kg soil of each element. This resulted in the best results as compared with other treatment.